2008
DOI: 10.1111/j.1525-1470.2008.00645.x
|View full text |Cite
|
Sign up to set email alerts
|

Nail Changes in Langerhans Cell Histiocytosis: A Possible Marker of Multisystem Disease

Abstract: We describe a child with a 6-month history of onycholysis, subungual hyperkeratosis, and hemorrhages in most of her fingernails and toenails. Nail involvement preceded the identification of osteolytic lesions at the mastoid on a cranial computed tomography scan, which was performed because of repeated episodes of acute otitis media. Some weeks later, a small number of erythematous papules developed over the trunk and face. The diagnosis of Langerhans cell histiocytosis was made by histopathologic examination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…To our knowledge, 21 previous cases of LCH with nail changes have been reported in the literature (Table 1). [4][5][6][9][10][11][12][13][14][15][16][17][18][19][20] As in other studies, 4,14,16,18,19 histopathologic differences between skin and nail lesions of LCH were not observed in our patient, but secondary change of acute inflammatory crusting was seen in the nail specimen.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…To our knowledge, 21 previous cases of LCH with nail changes have been reported in the literature (Table 1). [4][5][6][9][10][11][12][13][14][15][16][17][18][19][20] As in other studies, 4,14,16,18,19 histopathologic differences between skin and nail lesions of LCH were not observed in our patient, but secondary change of acute inflammatory crusting was seen in the nail specimen.…”
Section: Discussionsupporting
confidence: 69%
“…Opposition to this theory was posed by Jain in 2000, who instead suggested that nail changes tend to occur in patients with multisystem disease and involvement of high‐risk organs, which is known to be significantly related to mortality. Therefore, nail changes did not independently indicate a poor prognosis, and in fact reported cases of nail changes not associated with multisystem disease showed excellent response to chemotherapy . Clearing of the nail abnormalities with chemotherapy is thought to depend on the extent of involvement of the nail matrix and seems to be distinct from response obtained to chemotherapy in other organs …”
Section: Discussionmentioning
confidence: 98%
“…The clinical features comprise hemorrhagic and pustular lesions in the nail plate, longitudinal grooving, hyperkeratosis, subungual thickening, striate nail dystrophy, onycholysis, paronychia, and loss of nail plate 2, 3, 4, 5, 6…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, 18 cases have been documented in the literature to date. According to most cases reported, it is thought to indicate a poor prognosis 2, 3, 4, 5, 6. We report the case of a child with nail lesions, which led to a diagnosis of LCH.…”
Section: Introductionmentioning
confidence: 86%
“…Involvement of the nails, which was observed in two paediatric patients of our cohort, can be erroneously attributed to various diseases. 41 Posterior pituitary involvement resulting in DI can occur before, concurrently, or after LCH diagnosis. 4 In our study, DI was diagnosed in 5.0% of paediatric patients at disease presentation.…”
Section: Discussionmentioning
confidence: 99%